Association between inflammatory markers and non-alcoholic fatty liver disease in obese children - Duan, Yamei; Luo, Jiayou; Pan, Xiongfeng; Wei, Jia; Xiao, Xiang; Li, Jingya; Luo, Miyang (Frontiers in Public Health, 2022)
Background Given the high prevalence of non-alcoholic fatty liver disease (NAFLD) in obese children, non-invasive markers of disease to date are still limited and worth exploring. Objective This study aimed to evaluate the association between inflammatory markers and NAFLD in obese children. Methods We performed a case-control study in Hunan Children's Hospital from September 2020 to September 2021. Study participants were children with obesity diagnosed with NAFLD by abdominal ultrasound examination. Mean platelet volume (MPV), platelet distribution width (PDW), neutrophil, lymphocyte, monocyte, and platelet counts were extracted from medical records and inflammatory cytokines were measured by enzyme-linked immunosorbent assay (ELISA). Multivariable logistic regression analysis was performed to evaluate the association between inflammatory markers and NAFLD. We also used receiver operating characteristic curve analysis to assess the discriminative ability of inflammatory cytokines for NAFLD. Results Two hundred and sixty-seven obese children were enrolled, including 176 NAFLD patients and 91 simple obesity controls. Multivariable logistic model indicated that increased interleukin (IL)-1β [odds ratio (OR) = 1.15, 95% confidence interval (CI): 1.04–1.27], IL-6 (OR = 1.28, 95% CI: 1.07–1.53), and IL-17 (OR = 1.04, 95% CI: 1.02–1.07) levels were significantly associated with NAFLD. In contrast, we observed non-significant associations for IL-8, IL-12, IL-21, IL-32, tumor necrosis factor-α (TNF-α), neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR), mean platelet volume (MPV), and platelet distribution width (PDW) with NAFLD. The area under the curves (AUCs) of IL-1β, IL-6, and IL-17 to discriminate obese children with or without NAFLD were 0.94, 0.94, and 0.97, respectively. Conclusions Our results indicated that IL-1β, IL-6, and IL-17 levels were significantly associated with NAFLD. These inflammatory cytokines may serve as non-invasive markers to determine the development of NAFLD and potentially identify additional avenues for therapeutic intervention.